Repellent Activity Test Of Essential Oil Gel Of Cinnamommum Burmanii Bi Leaves Against Aedes Aegypti Mosquitoes - Bayuadi Bayuadi; Purwati Purwati; Riong Seulina Panjaitan (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2022)
Cinnamomum burmanni BI leaf is known to have high eugenol content, eugenol able to resist the bite of Aedes aegypti mosquito as a vector of Dengue Hemorrhagic Fever. Research on test of repellent activity of gel oil Cinnamomum burmanni BI leaf to Aedes aegypti mosquito is done to know its activity as a repellent preparation against Aedes aegypti mosquito. In this research made the gel of essential oil of Cinnamomum burmanni BI leaf with base karbopol 940 made in 3 formula, F1 (7,50%); F2 (15,00%); F3 (30,00%) and use Positive Control repellent supply on the market and contains DEET. The three formulas produce a good gel in terms of physical stability, organoleptic, homogeneity, pH, viscosity, and scattering, but all formulas cause irritation. The test of repellent activity against Aedes aegypti mosquito done for 4 hours with 5 repetitions showed Cinnamomum burmanni BI leaf oil formula F3 (30,00%) had repellent activity against Aedes aegypti mosquito with high protection 94,01% for 4 hours.